Pelatihan Umkm Pada Desa Sumber Rejo, Kabupaten Semarang, Jawa Tengah - Fitria Marisya; Marsinah Marsinah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
This training discusses human resource management (HR) in the digital era and efforts to increase the productivity of small and medium enterprises (SMEs). This training involves analyzing the competencies required by human resources professionals and their role in designing effective strategies and policies for HR management in organizations. Apart from that, this training also highlights the challenges faced by SMEs, especially in terms of low levels of productivity, added value and product quality. The training results show that human resources professionals need to master strategic competencies which include an understanding of organizational values, talent management, leadership, and the use of digital technology. Apart from that, it is also important for them to be able to position the business strategically, build relationships based on trust, and manage various pressures in the business. This training provides valuable insight for human resources professionals and SME stakeholders in understanding the importance of HR management in the digital era and increasing SME productivity. Implementing effective strategies in managing human resources and increasing productivity will help achieve the goals of sustainable SME development and a more significant contribution to the national economy.